Effectiveness of internal audit as an instrument for improving management in the public sector: A case study of Kibaha town council, - Mosha, Angel (2024)
A dissertation submitted in partial fulfillment of the requirements for the award of the Degree of Master of Science in Accounting (MSc-A&F) and Finance of Mzumbe University Dar es Salaam campus college.